Guide on Developing Climate-Smart Map and Adaptation Plan (CS-MAP) - English Version - Ministry of Agriculture and Rural Development, Vietnam; CGIAR Research Program on Climate Change, Agriculture and Food Security (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
The English version of the instructional video (originally in Vietnamese language) on how to develop and implement the Climate-Smart Map and Adaptation Plan (CS-MAP). Using participatory tools, CS-MAP serves as a guide for local communities to develop their own risk maps and adaptive plans, which cater to their respective local contexts. The five key steps to develop the CS-MAP are: (1) define climate-related risks; (2) define the border of risk extents; (3) recommend adaptation plans; (4) modify climate-smart maps and adaptation plans; and (5) integrate outcomes at the sub-regional and regional levels. This video is produced by CCAFS Southeast Asia and the Department of Crop Production-Ministry of Agriculture and Rural Development.